The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1182/blood.v114.22.3542.3542
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Mobilization of Murine Hematopoietic Stem and Progenitor Cells with TG-0054, a Novel CXCR4 Antagonist.

Abstract: 3542 Poster Board III-479 Background The interaction between SDF-1 and its receptor, CXCR4, is responsible for retaining of stem cells in the bone marrow. CXCR4 antagonist disrupts the SDF-1/CXCR4 interaction and mobilizes CD34+ hematopoietic stem cells (CD34+ HSCs) and CD133+ endothelial progenitor cells (CD133+ EPCs) from bone marrow into circulation, which can be used as a source for stem cell transplantation and other potential clinical ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…To ensure that TG-0054, which was shown to mobilize HSCs in mice and humans (11, 22), was effective in mobilizing CXCR4+ stem cells in minipigs, we analyzed PB cell components after TG-0054 treatment (two intravenous doses of 2.85 mg/kg TG-0054 of 72 h apart). TG-0054 increased PB white blood cell (WBC) counts, which peaked at 0.5 and 1 h after the first dose and the second dose, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To ensure that TG-0054, which was shown to mobilize HSCs in mice and humans (11, 22), was effective in mobilizing CXCR4+ stem cells in minipigs, we analyzed PB cell components after TG-0054 treatment (two intravenous doses of 2.85 mg/kg TG-0054 of 72 h apart). TG-0054 increased PB white blood cell (WBC) counts, which peaked at 0.5 and 1 h after the first dose and the second dose, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…TG-0054 is a CXCR4 antagonist and was reported to mobilize BM HSCs (22). It is being evaluated for treating human BM malignancies (35, 36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this process took several days and the effect of GC‐SF has broad interindividual variability . AMD3100, a representative CXCR4 antagonist, can effectively and rapidly mobilize HSCs, including EPCs . However, HSCs mobilized by AMD3100 showed obviously impaired survival after transplantation , and severe cardiac toxicity has been reported after long‐term AMD3100 administration .…”
Section: Introductionmentioning
confidence: 99%
“…SDF-1 serves as a specific ligand to CXCR4, a G protein-coupled receptor with seven transmembrane domains on the surface of many stem cell types. , The CXCR4/SDF-1 axis has been well-known to regulate cancer metastasis, stem cell homing, trafficking, and mobilization. Thus, CXCR4 antagonists that mobilize various stem cells, including hematopoietic stem cells (HSCs), endothelial progenitor cells (EPCs), and mesenchymal stem cells (MSCs), out of the bone marrow into the peripheral blood, might potentially serve as therapeutic agents to treat AKI either via autologous transplantation or simply by raising stem cell levels in blood . Indeed, such cell-based therapy concept has been validated by a selective CXCR4 antagonist, a small molecule known as AMD3100 (Plerixafor, compound 1 ). Approved by the U.S. FDA in December 2008, a regimen combining compound 1 with granulocyte colony-stimulating factor (G-CSF, Filgrastim) that synergistically augments stem cell mobilization has been used for autologous transplantation of CD34 + cells (HSCs) in patients suffering multiple myeloma or non-Hodgkin’s lymphoma. Such procedures allowed rapid restoration of immune system after undergoing destructive radio- or chemotherapy. Moreover, other findings revealed that compound 1 could effectively ameliorate the injured regions caused by myocardial infarction or ischemic stroke, suggesting that CXCR4 antagonists might have great therapeutic potential in anti-inflammation and/or tissue repair. Though many small molecules and peptidomimetics have been successfully developed to target CXCR4 receptors, , only a fraction of them (Figure ), including TG-0054 (phase II), AMD070 (phase I/II), MSX-122 (phase I), BL8040 (T140) (phase I/II), LY2510924 (phase II), CTCE-9908 (phase I/II), and POL6326 (phase I/II), have entered clinical development. These clinical candidates mainly act as HIV entry inhibitors or stem cell mobilizers for autologous transplantation.…”
Section: Introductionmentioning
confidence: 99%